CRISPR-based screening & functional characterization of long non-coding RNAs in melanoma - Petroulia, Stavroula (Technische Universität Dortmund, 2024)
Melanoma, the most lethal form of skin cancer, is increasingly prevalent in Western populations and is characterized by its high metastatic potential. This cancer type is distinguished by a significant accumulation of somatic mutations, primarily due to UV radiation, leading to a mutation rate that exceeds that of most other solid tumors. The progression of melanoma involves the uncontrolled proliferation and spread of malignant melanocytes, with notable disruptions in the MAPK-ERK and PI3K-AKT-mTOR signalling pathways contributing to the development of advanced therapeutic strategies. Recent research has highlighted the importance of the non-coding regions of the genome, previously considered "junk DNA", for their regulatory functions. Long non-coding RNAs (lncRNAs), which are typically longer than 200 nucleotides, have been identified as key players in cellular development, differentiation, and cancer progression. Numerous studies have established a link between lncRNAs and the growth and progression of melanoma, with elevated lncRNA expression levels observed in melanoma cases. Herein, the present study attempted to elucidate the involvement of a specific set of lncRNAs in mechanisms underlying cell growth and proliferation. These lncRNAs, which had been observed to exhibit increased expression in melanoma cell lines and in short-term cultures derived from brain and lymph node metastasis, are examined by employing CRISPRi screening. Furthermore, functional characterization analyses were conducted on the most promising lncRNA candidates, including BDNF-AS, GMDS-AS1, and a novel, non-annotated lncRNA named XLOC030781 based on preliminary data that validate their importance in melanoma. Suppression of these lncRNAs led to apoptosis and inhibited cell cycle progression, with XLOC030781 playing a notable role in melanoma migration, broadening its functional scope in relation to this malignancy. Finally, the implementation of fluorescence in situ hybridization technique provided data on their subcellular localization, offering complementary information on their functionality.
Keywords: Melanoma; Non-coding RNAs; CRISPRi screen; 540; Melanom; Non-coding RNA